Determinants of Firm Value in the Coal Industry: Stock Price, Firm Size, Profitability, and Leverage 2021-2023 - Iskandar, Luis; Dwi Nur Arofah, Berliani; Dhea Parlina, Nurhana (DINASTI RESEARCH, 2025)
This study had the aim to examine the influence of stock price, company size, profitability, along with leverage on firm value in coal mining sub-sector companies that are listed on the Indonesia Stock Exchange during 2021–2023 period. A quantitative method with a purposive sampling approach was employed, resulting in 51 observations from 17 companies. The variables analyzed include stock price (closing price), company size (SIZE), profitability (ROA), and leverage (DAR), with firm value proxied by the Price to Book Value (PBV) ratio. Data were analyzed through multiple linear regression with the assistance of IBM SPSS 25 software. The findings revealed that all independent variables collectively have a significant impact on firm value, with a coefficient of determination of 49.5%. However, on a partial basis, only profitability and leverage exhibit a significant influence, both showing a negative relationship with firm value. These findings highlight the importance of maintaining an efficient financial structure and closely monitoring internal financial performance to enhance firm value. This study offers practical insights for investors, corporate management, and regulators in understanding the key drivers of firm value within the coal mining industry.